Productivity and profitability of soybean (Glycine max) as influenced by site-specific nutrient management - Kaur, Navneet; Singh, Janardan; Shilpa, Shilpa (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during the rainy season of 2018 at CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur to study the effect of site-specific nutrient management on yield attributes, productivity and profitability of soybean. The experiment was laid out in randomized block design comprising of seven treatments (N43P43K50, N43P43K0, N43P0K50, N0P43K50, N20P60K40, FYM@5t/ha and N0P0K0). Experimental site was silty clay loam in texture, acidic in reaction, low in available nitrogen, and medium in available phosphorus and potassium.The highest number of pods (71/plant), seed yield (2 t/ha), net return (45.9Ã—103 `//ha), benefit cost ratio (2.25) and profitability (366.9 `//ha/day) was recorded at N43P43K50. Omission of nutrients significantly reduced productivityand profitability of soybean. The lowest number of pods, seed yield, net return,benefit cost ratio and profitability was recorded in control treatment (N0P0K0). Site specific nutrient management (N43 P43 K50) proved to be the best treatment in enhancing the yield and profitability of soybean.The recommended dose of fertilizers (N20P60K40) and farmer’s practice (FYM@5t/ha) proved to be the second and third best treatment, respectively.